Spatial Upscaling-Based Algorithm for Detection and Estimation of Hazardous Gases - Srivastava, Sumit; Chaudhri, Shiv Nath; Rajput, Navin Singh; Alsamhi, Saeed Hamood; Shvetsov, Alexey V. (Institute of Electrical and Electronics Engineers Inc., 2023)
Recently, society/industry is getting smarter and sustainable through artificial intelligence-based solutions. However, this rapid advancement is also polluting our air ambience. Hence real-time detection and estimation of hazardous gases/odors in the air ambiance has become a critical need. In this paper, a convolutional neural network (CNN) based multi-element gas sensor arrays signature response analysis approach has been presented to achieve higher accuracy in detection and estimation of hazardous gases. Accordingly, the real-time gas sensor array responses are spatially upscaled and processed on the edge, using lightweight CNNs. For the verification of our hypothesis, we have used a four-element metal-oxide semi-conductor (MOS)-based thick-film gas sensor array, fabricated by our group, by using SnO2, ZnO, MoO, CdS materials for detection and estimation of four target hazardous gases, viz., acetone, car-bon-tetrachloride, ethyl-methyl-ketone, and xylene. The four-element (2×2) raw sensor responses are first upscaled to 6×6 responses and a lightweight CNN is trained on 42 samples of 6×6 input vectors. The trained system is then tested using 16 unknown (not used during training) test samples of the considered gases/odors. All the 16 test samples are detected correctly. The Mean Squared Error (MSEs) of detection has been 1.42×10-14 while the estimation accuracy of 2.43× 10-3 were achieved for the considered gases. Our designed system is generic in design and can be extended to other gases/odors of interest.
This paper published with affiliation IIT (BHU), Varanasi in Open Access Mode.
Keywords: convolutional neural networks (CNNs); electronic nose; gas sensor array; Internet of Things (IoT); Spatial upscaling